Effects of walnut-enriched diet on blood lipids and glucose profiles in hyperlipidemic subjects: a randomized-controlled trial - Okburan, Gozde; Mercanlıgil, Seyit Mehmet; Kabaran, Seray; Ogmen, Sultan (Progress in Nutrition, 2019)
Background and Objectives: Walnuts have been shown to reduce serum lipids in hyperlipidemic individuals with a well-controlled feeding trials. Current study have been determined the effects of daily walnut consumption on serum lipids, fasting glucose and insulin levels in hyperlipidemic subjects. Subjects and Methods: In this, randomized controlled trial, mild to moderate hyperlipidemic subjects were randomly divided into 2 groups as walnut-enriched (n=20) and control (n=17) groups for 6 weeks. All subjects adhered to a medical nutrition therapy as low-fat and low-cholesterol diet. The walnut-enriched group was supplemented with 40 g/day of walnuts added to their diets. In order to follow nutritional and physical activity status of all subjects, they were visited every 15 days (in total 4 times). Anthropometric measurements of the subjects were taken and were monitored at each visit during the study. Blood samples were measured at the beginning and at the end of the study. Results: Our study showed that enriching a well controlled diet with walnuts (40g/day) improves the plasma lipid as well as serum glucose levels after the 6-week. Both groups showed a decrease in serum lipids with adaptation to the AHA (Americen Heart Association) diet, but statistically significant reductions (p